2021
DOI: 10.1016/j.tifs.2021.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of heritage food concept

Abstract: This article is made publicly available in the institutional repository of Wageningen University and Research, under the terms of article 25fa of the Dutch Copyright Act, also known as the Amendment Taverne. This has been done with explicit consent by the author.Article 25fa states that the author of a short scientific work funded either wholly or partially by Dutch public funds is entitled to make that work publicly available for no consideration following a reasonable period of time after the work was first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 45 publications
1
25
0
Order By: Relevance
“…According to the analysis, side effects can occur when promoters of valorisation initiatives prompt a priori transformations of the product by selecting only those material and immaterial elements in line with the alleged tastes of new customers and leaving aside the complex social and cultural values that link a product to a specific foodscape. As already observed by Almansouri et al [29], the triggering of these dynamics can erode and distort distinguishing features of heritage foods and their authenticity.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…According to the analysis, side effects can occur when promoters of valorisation initiatives prompt a priori transformations of the product by selecting only those material and immaterial elements in line with the alleged tastes of new customers and leaving aside the complex social and cultural values that link a product to a specific foodscape. As already observed by Almansouri et al [29], the triggering of these dynamics can erode and distort distinguishing features of heritage foods and their authenticity.…”
Section: Discussionmentioning
confidence: 62%
“…To date, some studies have analysed the debate on "food as cultural heritage" in order to frame this concept and explore the perspectives of its valorisation (i.e., the process that aims at increasing the economic, social, and cultural value of a product) [28], as well as to define the main dimensions of heritage foods and identify some of the risk factors that may compromise their authenticity and food safety [29]. However, little attention has been paid thus far to investigating when food heritagisation and the valorisation of food heritage may fail in achieving social and cultural sustainability goals.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that heritage food refers to the physical chunk used to prepare food and consumption (Almansouri et al, 2021) that is important for rural areas as it is strongly related to villager's identity, and specifically, to food production. Almansouri et al (2021) emphasised that heritage food reflects shared memory and origins, which support a feeling of belonging to a territory, how the dishes are prepared, and who prepares them. This also includes preparation, ingredients, recipes, and the context, such as serving and presenting the food.…”
Section: Discussionmentioning
confidence: 99%
“…The charm of heritage food is also compromised due to the disconnection of the feelings of the young generation as they are not familiar with or not attracted to the food compared to the contemporary selection available. Although the importance of heritage cuisine is becoming more significant, the concept of heritage food remains unclear, and there is still a scarcity of information on heritage food (Almansouri et al, 2021). The current study explored the heritage foods in Kedah and investigated if food dishes have continuity from ancestors to the present generation.…”
Section: Introductionmentioning
confidence: 99%
“…It is a sort of culinary hybrid between pulque and mescal, but it is unclear which agave species was used. This information could be crucial to recover this apparently lost food, which could be a lost knowledge to humanity [188][189][190][191].…”
Section: Reviewed Distribution Of the Tmfbmentioning
confidence: 99%